Analysis of factors contributing to low vaccination coverage among school-aged children - Silviani Dewi; Mustopa Mustopa; Elfira Husna; Fauzi Asra; Erian Fatria; Asrul Fahmi; Irna Nursanti (Program Studi Ilmu Keperawatan-fakultas Ilmu Kesehatan Universitas Malahayati, 2025)
Background: The School-Age Children Immunization Month program is an annual national vaccination initiative targeting school-aged children in Indonesia. However, a decline in vaccination coverage has been observed in recent years, influenced by both internal and external factors. Key contributing variables include maternal knowledge, maternal attitudes, cultural beliefs, and the roles of healthcare workers, teachers, and parents. Purpose: To analyze the factors most significantly associated with low vaccination coverage among elementary school children. Method: A quantitative, cross-sectional design was employed. A total of 142 respondents—mothers of elementary school students in grades 1, 2, and 5—were selected using simple random sampling. Data were collected using a structured questionnaire. Statistical analyses included univariate analysis, bivariate analysis using the chi-square test, and multivariate analysis using logistic regression. Results: Five variables met the criteria for inclusion in the multivariate analysis (p < .25): maternal knowledge, maternal attitude, cultural beliefs, the role of healthcare workers, and the role of parents. Logistic regression analysis identified the parental role as the most significant predictor of vaccination coverage (p = .000; OR = 2.234), indicating that children were more than twice as likely to be vaccinated when parental involvement was strong. Conclusion: Parental involvement emerged as the most influential factor affecting vaccination uptake among elementary school children. Strengthening parental support and engagement is crucial to improving vaccination coverage in school-based programs.